2015
DOI: 10.1371/journal.pone.0132605
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tai Chi on Physical and Psychological Health of College Students: Results of a Randomized Controlled Trial

Abstract: ObjectiveTo investigate the effectiveness and safety of Tai Chi Chuan (TCC) on physical and psychological health of college students.MethodsTwo hundred six college students were recruited and randomly allocated to a control group or a TCC exercise group in an equal ratio. Participants in the control group were instructed to maintain their original activity level and those in the TCC exercise group received 12 weeks of TCC exercise training based on their original activity level. Physical and psychological outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 40 publications
(38 reference statements)
2
89
0
Order By: Relevance
“…Table 1 summarizes the characteristics of studies eligible for inclusion. Among the 26 RCTs ( Braithwaite & Fincham, 2009 ; Chase et al, 2013 ; Cheng et al, 2015 ; Chiauzzi et al, 2008 ; Erogul et al, 2014 ; Fontana et al, 1999 ; Franklin & Franklin, 2012 ; Gortner, Rude & Pennebaker, 2006 ; Hamdan-Mansour, Puskar & Bandak, 2009 ; Higgins, 2006 ; Jones & Johnston, 2000 ; Kanji, White & Ernst, 2006 ; Kattelmann et al, 2014 ; Kenardy, McCafferty & Rosa, 2006 ; Li et al, 2015 ; Mak et al, 2015 ; Pachankis & Goldfried, 2010 ; Peden et al, 2001 ; Reavley et al, 2014 ; Rohde et al, 2014 ; Seligman et al, 1999 ; Seligman, Schulman & Tryon, 2007 ; Shapiro et al, 2011 ; Vazquez et al, 2012 ; Yang et al, 2014 ; Zheng et al, 2015 ), CBT-related interventions were assessed in 11 studies, while mind–body-related and psycho-educational-related interventions were assessed in 10 and five studies, respectively. Universal and selective delivery levels were equally present ( k = 13 for both).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of studies eligible for inclusion. Among the 26 RCTs ( Braithwaite & Fincham, 2009 ; Chase et al, 2013 ; Cheng et al, 2015 ; Chiauzzi et al, 2008 ; Erogul et al, 2014 ; Fontana et al, 1999 ; Franklin & Franklin, 2012 ; Gortner, Rude & Pennebaker, 2006 ; Hamdan-Mansour, Puskar & Bandak, 2009 ; Higgins, 2006 ; Jones & Johnston, 2000 ; Kanji, White & Ernst, 2006 ; Kattelmann et al, 2014 ; Kenardy, McCafferty & Rosa, 2006 ; Li et al, 2015 ; Mak et al, 2015 ; Pachankis & Goldfried, 2010 ; Peden et al, 2001 ; Reavley et al, 2014 ; Rohde et al, 2014 ; Seligman et al, 1999 ; Seligman, Schulman & Tryon, 2007 ; Shapiro et al, 2011 ; Vazquez et al, 2012 ; Yang et al, 2014 ; Zheng et al, 2015 ), CBT-related interventions were assessed in 11 studies, while mind–body-related and psycho-educational-related interventions were assessed in 10 and five studies, respectively. Universal and selective delivery levels were equally present ( k = 13 for both).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of studies eligible for inclusion. Among the RCTs (Braithwaite & Fincham 2009;Chase et al 2013;Cheng et al 2015;Chiauzzi et al 2008;Erogul et al 2014;Fontana et al 1999;Franklin & Franklin 2012;Gortner et al 2006;Hamdan-Mansour et al 2009;Higgins 2006;Jones & Johnston 2000;Kanji et al 2006;Kattelmann et al 2014;Kenardy et al 2006;Li et al 2015;Mak et al 2015;Pachankis & Goldfried 2010;Peden et al 2001;Reavley et al 2014;Rohde et al 2014;Seligman et al 1999;Seligman et al 2007;Shapiro et al 2011;Vazquez et al 2012;Yang et al 2014;Zheng et al 2015), CBT-related interventions were assessed in 11 studies, while mind-body-related and psycho-educationalrelated interventions were assessed in 10 and 5 studies, respectively. Universal and selective delivery levels were equally present (k=13 for both).…”
Section: Resultsmentioning
confidence: 99%
“…If the supporting leg does not possess the ability to stabilize the body, the working leg cannot attain a favourable external opening angle, and attaining a clean, beautiful, and correct rotation becomes relatively difficult. A review study also reported that physical training in addition to traditional dance training may contribute to dancer's movement range of motion [20,21]. Finally, the improvement in the supporting leg plantar flexion angle of the training group was superior to that of the control group.…”
Section: Discussionmentioning
confidence: 95%